Health Risks Assessment of Rainwater Pollutants in Jengka, Pahang, Malaysia - Nadzifah Ghazali, Siti; Razman, Fazrul; Zahari Abdullah, Mohd (International Journal of Engineering and Technology, 2018)
Rainwater samples were collected in Jengka, Pahang Malaysia. Temperature, pH, TDS, EC, Al, Cu, Mn, and Zn were measured. The concentrations of heavy metals (Al, Cu, Mn and Zn) in thirty-eight samples were analysed using inductively coupled plasma-mass spectrometry (ICP-MS). Statistical analysis results indicate that pH, TDS, and EC showed significant differences between wet and dry seasons. However, no significant difference was observed seasonally for heavy metals (HMs). All parameters, except pH, were below the Malaysian Drinking Water Guidelines (MDWG) value and the health risk assessment for HMs indicates the safe levels. Principal component analysis (PCA) suggests that HMs in rainwater in Jengka, Pahang were originated from natural and anthropogenic sources.Â Â